Risk Factors for Therapeutic Failure and One-Year Mortality in Patients with Intramedullary Nail-Associated Infection after Trochanteric and Subtrochanteric Hip Fracture Repair - Bernadette Pfang; Marco A. Villegas García; Antonio Blanco García; Álvaro Auñón Rubio; Jaime Esteban; Joaquín García Cañete (MDPI AG, 2024)
Despite the implications of trochanteric and subtrochanteric intramedullary (IM) nail infection for patients with hip fracture, little is known about risk factors for therapeutic failure and mortality in this population. We performed a retrospective observational analysis including patients diagnosed with trochanteric and subtrochanteric IM nail infection at a Spanish academic hospital during a 10-year period, with a minimum follow-up of 22 months. Of 4044 trochanteric and subtrochanteric IM nail implants, we identified 35 cases of infection during the study period (0.87%), 17 of which were chronic infections. Patients with therapeutic failure (n = 10) presented a higher average Charlson Comorbidity Index (CCI) (5.40 vs. 4.21, p 0.015, CI 0.26-2.13) and higher rates of polymicrobial (OR 5.70, p 0.033, CI 1.14-28.33) and multidrug-resistant (OR 7.00, p 0.027, CI 1.24-39.57) infections. Upon multivariate analysis, polymicrobial infection and the presence of multidrug-resistant pathogens were identified as independent risk factors for therapeutic failure. Implant retention was associated with an increased risk of failure in chronic infection and was found to be an independent risk factor for overall one-year mortality in the multivariate analysis. Our study highlights the importance of broad-spectrum empirical antibiotics as initial treatment of trochanteric and subtrochanteric IM nail-associated infection while awaiting microbiological results. It also provides initial evidence for the importance of implant removal in chronic IM-nail infection.